2011
DOI: 10.1021/am200782x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of AuPt Alloy Foam Films and Their Superior Electrocatalytic Activity for the Oxidation of Formic Acid

Abstract: AuPt alloy films with three-dimensional (3D) hierarchical pores consisting of interconnected dendrite walls were successfully fabricated by a strategy of cathodic codeposition utilizing the hydrogen bubble dynamic template. The foam films were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Due to the special porous structure, the electronic property, and the assembly effect, the AuPt alloy foam films show superior electrocatalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 70 publications
3
81
0
1
Order By: Relevance
“…1 (C, D) show many nanoparticles with 2050 nm and 2060 nm sizes uniformly distributed on the AuNPs/GCE (C) and Au-PtNPs/GCE (D) surfaces, respectively. The Pt/Au atomic ratio is calculated to be 1.46:98.54 according to the EDX spectra, being slightly larger than the Pt/Au concentration ratio in the feeding solution (1:500), as reported before [18]. The EDX elemental mapping proves that Pt and Au sites were uniformly distributed on the Au-PtNPs/GCE (Insets of Fig.…”
Section: Resultssupporting
confidence: 71%
“…1 (C, D) show many nanoparticles with 2050 nm and 2060 nm sizes uniformly distributed on the AuNPs/GCE (C) and Au-PtNPs/GCE (D) surfaces, respectively. The Pt/Au atomic ratio is calculated to be 1.46:98.54 according to the EDX spectra, being slightly larger than the Pt/Au concentration ratio in the feeding solution (1:500), as reported before [18]. The EDX elemental mapping proves that Pt and Au sites were uniformly distributed on the Au-PtNPs/GCE (Insets of Fig.…”
Section: Resultssupporting
confidence: 71%
“…The peaks in Fig. 3(b) at 84.1/87.8 eV can be assigned to Au 0 4f 5/2 /4f 7/2 [55,56]. The C 1s spectrum shown in Fig.…”
Section: Xps Analyses For the Electrodeposited Superhydrophobic Metalmentioning
confidence: 93%
“…Xu and co-workers [21] studied the electrocatalytic activity of PtAu alloy nanoparticles with 1:1 atomic ratio and demonstrated that the PtAu/C catalyst exhibited a higher activity for FA oxidation reaction than commercial Pt/C. Liu et al [34] developed a 3D porous AuPt alloy foam film catalyst with superior electrocatalytic activity toward FA oxidation. Huang et al [35] prepared a PtAu alloy catalyst by electrodeposition method for FA electrooxidation with the dehydration pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the surface composition of atomic Pt/Au ratio and the preparation method are significantly related to the electrocatalytic activity of bimetallic PtAu catalyst for FA oxidation reaction [13,[34][35][36]. In general, the high electrocatalytic activity of bimetallic PtAu catalyst has been ascribed to the special electronic effect [29,36,37], ensemble effect [11,20,30], and synergistic effect [34,38,39]. Many research findings have revealed that both Pt-onAu and PtAu alloy catalysts exhibited high electrocatalytic activity toward FA oxidation with much less CO ads than that on Pt catalyst surface.…”
Section: Introductionmentioning
confidence: 99%